Experiment results of a two-by-two diverse antenna system over sea surface in NLOS scenario - Dong, Feng (2013)
This paper presents the experimental study of a sea-to-land NLOS link at 5.5GHz over the sea path. The transmitter is installed on board a boat and the receiver is located at the top of a building on the shore. Channel performance under NLOS scenario using antenna diversity setup is examined. Measurement results are then shown statistically. It is found that the diversity scheme can help improve the communication link significantly.